Three-Dimensional Prototyping with PLA for the Electrical Sector: Perspectives and Challenges in Material Development - Diana Aline Gomes; Luís Fernando Cusioli; Daniel Mantovani; Angelo Marcelo Tusset; Silvio Miguel Parmegiani Marcucci; Giane Gonçalves Lenzi; Antonio Benjamim Mapossa; Rosângela Bergamasco (Energies)
Additive manufacturing with polylactic acid (PLA) presents significant potential for the electrical sector, especially in rapid prototyping and customized component fabrication. While PLA is valued for its biodegradability and ease of processing, its limited thermal stability and poor electrical conductivity restrict its use in high-performance applications. This study investigates the enhancement of PLA through the incorporation of conductive and thermally resistant fillers, aiming to expand its functional properties. Advances in multimaterial and 4D printing are also explored as strategies to increase the applicability of PLA in the production of sensors, flexible circuits, and tailored electrical devices. The findings support PLA’s potential as a sustainable, high-value material for next-generation electrical manufacturing.